Isolation of the New Antiplasmodial Butanolide, Malleastrumolide A, from Malleastrum sp. (Meliaceae) from Madagascar. Issue 12 (15th December 2017) - Du, Yongle; Abedi, Alexander K.; Valenciano, Ana Lisa; Fernández‐Murga, Maria L.; Cassera, Maria B.; Rasamison, Vincent E.; Applequist, Wendy L.; Miller, James S.; Kingston, David G. I.
Abstract : An extract of Malleastrum sp. (Meliaceae) collected in Madagascar by the Madagascar International Cooperative Biodiversity Group was found to have antimalarial activity, with an IC 50 value between 2.5 and 5 μg ml −1 . After purification by liquid‐liquid partition, chromatography on a Diaion open column, C 18 SPE and C 18 reversed phase HPLC, the new butanolide, malleastrumolide A, was isolated. The structure of malleastrumolide A was determined by mass spectrometry, NMR, and ECD. The double bond position was determined by cross‐metathesis and mass spectrometry. The compound has antiproliferative activity against the A2780 ovarian cancer cell line with an IC 50 value of 17.4 μm and antiplasmodial activity against the drug‐resistant Dd2 strain of Plasmodium falciparum with an IC 50 value of 2.74 μm . Abstract :